Incorporating Local Proverbs into English Lessons: Enhancing Cross-Cultural Awareness - Norpoʻlatova Nozima Yusufxon qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the integration of local proverbs into English lessons as a strategy to enhance cross-cultural awareness among EFL learners. Proverbs, as culturally rich expressions, reflect the values, beliefs, and traditions of a society. By introducing proverbs from learners’ native culture alongside English equivalents, teachers can foster a deeper understanding of both languages and promote intercultural competence. The study examines pedagogical methods for using proverbs in vocabulary, speaking, and writing activities, highlighting their role in motivating learners, developing critical thinking, and enriching classroom discussions. Evidence from classroom practice and research suggests that incorporating proverbs strengthens linguistic skills while cultivating awareness of cultural similarities and differences. The article also discusses strategies for effective implementation in EFL classrooms.